Visual acuity and contrast sensitivity of adult zebrafish - Tappeiner Christoph; Gerber Simon; Enzmann Volker; Balmer Jasmin; Jazwinska Anna; Tschopp Markus (Frontiers in Zoology, 2012)
Abstract Background The aim of this study was to evaluate the visual acuity of adult zebrafish by assessing the optokinetic reflex. Using a modified commercially available optomotor device (OptoMotry®), virtual three-dimensional gratings of variable spatial frequency or contrast were presented to adult zebrafish. In a first experiment, visual acuity was evaluated by changing the spatial frequency at different angular velocities. Thereafter, contrast sensitivity was evaluated by changing the contrast level at different spatial frequencies. Results At the different tested angular velocities (10, 15, 20, 25, and 30 d/s) and a contrast of 100%, visual acuity values ranged from 0.56 to 0.58 c/d. Contrast sensitivity measured at different spatial frequencies (0.011, 0.025, 0.5, 0.1, 0.2, 0.3, 0.4, 0.5 and 0.55 c/d) with an angular velocity of 10 d/s and 25 d/s revealed an inverted U-shaped contrast sensitivity curve. The highest mean contrast sensitivity (±SD) values of 20.49 ± 4.13 and 25.24 ± 8.89 were found for a spatial frequency of 0.05 c/d (angular velocity 10 d/s) and 0.1 c/d (angular velocity 25 d/s), respectively. Conclusions Visual acuity and contrast sensitivity measurements in adult zebrafish with the OptoMotry® device are feasible and reveal a remarkably higher VA compared to larval zebrafish and mice.